2018
DOI: 10.1093/mnras/sty2034
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Kolmogorov-like magnetic energy spectrum in Tycho’s supernova remnant by two-point correlations of synchrotron intensity

Abstract: The spectral slope of the magnetic energy in supernova remnants (SNRs) can be obtained by analysis of spatial two-point correlation functions of synchrotron intensities. This method has been originally developed for the analysis of magnetic field structure in diffuse interstellar medium and applied when the geometry of the emission region is simple and known. In this paper, applying this correlation analysis to Tycho's SNR, for which the synchrotron emission region is known to be a spherical shell, we find tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
4
11
0
Order By: Relevance
“…This value is comparable to the power law index β = −8/3 predicted for two-dimensional in-compressible Kolmogorov turbulence (Kolmogorov 1941). This is also consistent with the findings of Shimoda et al (2018) who have analyzed the intensity fluctuations of a 1.4GHz VLA image of the Tycho SNR and found that the two-point correlation function in the outer shells of the SNR shows a scaling close to the Kolmogorov r 2/3 . This kind of power law scaling is also predicted for developed MHD turbulence (Goldreich & Sridhar 1995).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This value is comparable to the power law index β = −8/3 predicted for two-dimensional in-compressible Kolmogorov turbulence (Kolmogorov 1941). This is also consistent with the findings of Shimoda et al (2018) who have analyzed the intensity fluctuations of a 1.4GHz VLA image of the Tycho SNR and found that the two-point correlation function in the outer shells of the SNR shows a scaling close to the Kolmogorov r 2/3 . This kind of power law scaling is also predicted for developed MHD turbulence (Goldreich & Sridhar 1995).…”
Section: Discussionsupporting
confidence: 91%
“…In this paper we have interpreted the intensity fluctuations of the Kepler SNR as arising from MHD turbulence. At large angular scales the slope (β = −2.8) of the measured power spectrum is consistent with 2D Kolmogorov turbulence and also the angular two-point correlation of the Tycho SNR (Shimoda et al 2018). At small angular scales the slope (β = −3.1) for the Kepler SNR is consistent with earlier measurements for Cas A and Crab SNRs (Roy et al 2009) outcome of the complex morphology of the Kepler SNR (Figure 1).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the angular power spectrum estimates of Cas A and Crab obtained using TGE were found to be similar with the earlier results reported in Roy et al (2009). In another recent work, Shimoda et al (2018) have analysed VLA L-band image of the Tycho SNR to estimate the two-point correlation function of the specific intensity fluctuations. They have reported a Kolmogorov-like magnetic energy spectrum showing a scaling r 2/3 .…”
Section: Introductionsupporting
confidence: 84%
“…Note that this estimate of E is based on the coefficient at the Bohm limit, D(E) ≃ r g (E)c/3, that gives the shortest diffusion length for a given E. For Tycho's SNR, it is implied by the two-point correlation analysis of synchrotron intensity that the energy spectrum of downstream magnetic disturbances has a Kolmogorov-like scaling (Shimoda et al 2018b). 4 If this is also true for the upstream disturbances, the gyro factor ξ B may be greater than unity and the lower bound of E may be smaller than 33 TeV.…”
Section: Modelmentioning
confidence: 99%